Wound healing of different molecular weight of hyaluronan; in-vivo study - Fouda, Moustafa M G; Abdel-Mohsen, A M; Ebaid, Hossam; Hassan, Iftekhar; Al-Tamimi, Jameel; Abdel-Rahman, Rasha M; Metwalli, Ali; Alhazza, Ibrahim; Rady, Ahmed; El-Faham, Ayman; Jancar, J (International journal of biological macromolecules, 2016)
Recruitment of cells and mediators is altered during impaired wound healing, thereby delaying this process. To overcome this problem, the correlation of wound healing in older rats, and the impact of different molecular weight of hyaluronan without silver nanoparticles; (low-HA1), (High-HA2), (Medium- HA3) and with silver nanoparticles (High-HA4) is investigated. The superior HA were selected to be further investigated onto diabetic wounds. Our results pointed to a marked deficiency in wounds granulation in older rats, which was accompanied with impairment of healing process. In older rats group treated with HA2 or HA4, granulation and dermal construction were improved. Furthermore, the number of pathogenic bacteria on wounds was declined throughout the first 24h by HA2 and HA4. The wound size in HA4-treated older rats was significantly smaller than that in other HA1, HA2 or HA3-treated older ones. Also, diabetes impaired the level of inflammatory cytokine, in diabetic model. On contrary, HA4 was found to normalize the level of inflammatory cytokine, in the diabetic model. Furthermore, HA4 was found to recover all oxidative and toxicity markers in diabetic models. This data confirms the critical role of HA4 to improve granulation and inflammatory mediators in impaired older and diabetic rat wound healing.
Keywords: hojení ran; Diabetes Mellitus, Experimental; Humans; experimentální diabetes mellitus; molekulová hmotnost; Inflammation; krysa rodu Rattus; lidé; zvířata; Silver; kovové nanočástice; zánět; Wound Healing; stříbro; kyselina hyaluronová; Rats; Animals; Hyaluronic Acid; Metal Nanoparticles; Molecular Weight